PERBANDINGAN KOMPOSISI JENIS FITOPLANKTON ANTARA LAUT JAWA DAN BANDA - Yuneni, Ranny Ramadhani; Widianingsih, Widianingsih; Endrawati, Hadi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Pytoplankton in the waters has role as primary. Generally, the existence of phytoplankton in waters is supported by availability of light, nutrients, and other marine environment parameters. Java Sea is a sea that has shallow depth and Banda Sea has depth until more than 2000 meters. Many differences of characteristics, certainly organisms including phytoplankton, which are owned both the sea have different composition of phytoplankton, because of many factors influence it. The purpose of this research is study of comparison of phytoplankton spatial distribution horizontally between Java Sea and Banda Sea based on composition.Research was conducted in off shore of Java and Banda Sea. Data was collected with Research vessel of Baruna Jaya III was managed by BPPT (Balai Pengkajian dan Penerapan Teknologi) on 31th August – 9th September 2012. Methods used descriptive explorative. Phytoplankton was collected by plankton net passively that has mashes was 5 μm, lenght 65 cm, and diameter of meshes was 30 cm. Water was filtered as much as 30 l. result of filtering then stored in the bottle (200 ml). Station was collected as many as 14 stations. This Research was found 3 class of Phytoplankton, there were Bacillariophyceae (15 genera), Dinophyceae (4 genera), and Cyanophyceae (1 genera). The average abundance of Java Sea was 139 x 103 cells/m3 (range 115-189 x 103 cells/m3). Banda Sea had abundance range between 89-209 cells/m3 with average 146 x 103 cells/m3. Genera that had the highest of abundance was Rhizosolenia. The diversity index (H’) with range from 0,88 – 2,15 (very low – moderate). Uniformity index (e) values was with 0,67-0,88 (moderate-high), dominance index (D) was ranged from 0,12-0,51, just on station 17 that indicates dominating genus. Java and Banda Sea had identity community index (S) value was 76,47% (high category). Kruskal Wallis test (H) had values was 0,017 that lower than tabulated value of 6,63 at α = 0,01. It means accept H1 conclude that there is no significant difference of phytoplankton abundance between Java Sea and Banda Sea.